ATIVIDADE DE FORRAGEIO DE OPERÁRIAS DE Plebeia Catamarcensis. - VICENTE, Diego Mendonça; ARAÚJO, Gabriely Notário; PAULA-SILVA, Michele Castro; MICHELUTTI, Kamylla Balbuena; LIMA-JUNIOR, Sidnei Eduardo; ANTONIALLI-JUNIOR, William Fernando (ANAIS DO ENIC, 2025)
.